ABSTRACT THE EFFECT OF CREDIT AND LIQUIDITY RISK ON ISLAMIC BANK PROFITABILITY BY USING ISLAMIC INCOME AND PROFIT SHARING RATIO AS MODERATING VARIABLE - RAHMAYUNI (29010005) ; Pembimbing : Prof.Dr.Ir. Sudarso Kaderi Wiono, DEA., SARI
This paper examines the effect of sharia conformity in the relationship between bank risk with the profitability of Islamic Bank. This study motivated by the controversy of the result from the previous study about the effect of sharia conformity such as the profit loss sharing system in Islamic bank to the risk and profitability. The sample of this study was the commercial Islamic banks in Indonesia. The data was collected using purposive sampling method. The number of the sample were 3 Islamic commercial banks consist of Bank Muamalat, Bank Mandiri Syariah and Bank Mega Syariah Indonesia with the period of time from 2004 Ã‚Â– 2010. The sharia conformity was proxied by profit sharing ratio and Islamic income. The bank risk proxied by Credit risk and liquidity risk and the profitability of bank proxied by return on asset (ROA), return on equity (ROE) and profit margin (PM).The data were processing by using multiple regression analysis with SPSS 19 program. Beside using annual data, this study also uses quarterly data just to compare the result of the research. Many studies reveal that the system of profit sharing in Islamic banks influences bank risk. This analysis is done by using sharia conformity as moderating variables. Using data from three largest commercial Islamic Banks in Indonesia, the results indicate that on profit margin variablewe found thatonly profit sharing ratio moderate the relationship between credit risk and profitability of Islamic Banking. It isbecause of riskiness and uniqueness of profit loss sharing contract such as Mudharaba and Musyarakah, in practices it less popular among Islamic banks, especially on their asset side while on the liability side Islamic banks practices Mudharabah or Musharakah contract, on the asset side they prefer practices Murabahah contract (fixed-income modes of financing and installment sale), these deviations have led to increase riskiness.In the ROA, we found that only Islamic income moderate the relationship between liquidityrisk and ROA. This proves that the actual results of operations of Islamic banks are based on the principle of profit sharing will actually reduce the risk of bank liquidity. With ii profit sharing concept makes the borrowers and the lenders have a better benefit. But, a small liquidity risk could be due to a large portion fixed-income financing that provide more definitive results on the Islamic bank in Indonesia.The next dependent variable that is ROE, we found that the only profit sharing ratiomoderate the relationship between liquidity risk and ROE.This is because thebanksthat is used as samples in this studywere the threelargest Islamic banks in Indonesia with huge liquidity. It makes the liquidity risks faced by banks is low. In addition,the two tier mudharaba systemused by Islamic banks that more applied theprofit-loss sharing contractsto theliabilitiessideandfixed income contract on asset side makes therisks involvedwill be lower